Perfil de suscetibilidade e avaliação genotípica da resistência a β-lactâmicos em amostras de klebsiella pneumoniae isoladas de pacientes com infecção urinária adquirida na comunidade no Brasil - Patrícia Maria de Carvalho Campos (2018)
Klebsiella pneumoniae is a clinically relevant organism associated with the etiopathogenesis of both healthcare-associated infections and community acquired infections, including urinary tract infection (UTI). The microorganism is able to acquire and transfer antimicrobial resistance genes and consequently to this ability the bacterium emerged as a multidrug resistant pathogen. The most commonly employed antimicrobial drugs in the clinical routine are β-lactams and among enterobacteria the most important resistance mechanism is the production of β-lactamases enzymes. Considering the clinical relevance of K. pneumoniae, its association with community acquired UTI, and the spread of antimicrobial resistance, we developed this study aiming to evaluate the presence of blaKPC1,2,3, blaSHV, blaCTX-M, and blaTEM among 519 K. pneumoniae isolates obtained from community-acquired UTI patients, and to analyze the antimicrobial susceptibility profile of bacterial isolates. After boiling extraction of DNA, PCR was performed in order to search for the genetic markers described above. Data on the phenotypic antimicrobial susceptibility profile including the screening for extended spectrum β-lactamases (ESBLs) producing isolates and KPC were analyzed. The study revealed that 51.6% of K. pneumoniae isolates harbored at least one of the studied markers. The following relative frequencies were observed: blaSHV = 46.1%; blaCTX-M = 7.3%; blaTEM = 5.6%; blaKPC = 1.0%. Two and three of these genes were detected simultaneously in 6.0% and 1.2% of K. pneumoniae strains, respectively. In regard to the antimicrobial susceptibility profile the lowest resistant rate was detected for amikacin (0.2% resistance and 0.4% intermediate resistance) and the highest frequency of resistance was observed for ampicillin (100% resistance). Overall high susceptibility rates were detected, most of them higher than those previously reported. However it is noteworthy the resistance/intermediate resistance frequency to nitrofurantoin (30.3%). Among the 51 (9.8%) multiresistant isolates 41 presented at least one of the genes evaluated in this study suggesting that the synthesis of β-lactamases is associated with the resistance profile. Data generated reinforce that β lactamases production is a relevant resistance mechanism among K. pneumoniae associated with community-acquired UTI, since more than half of the study group harbored at least one of the four genes investigated. Besides this, even the narrow-spectrum β-lactamases, which are more prevalent in bacterial strains that circulate in the community, may interfere in the antimicrobial therapy outcome considering the commonly drug regimens used for the treatment of patients with community-acquired infections, such as first generation cephalosporins and penicillins. Data generated by this study contribute to understanding the epidemiology of UTI and to the designing of more efficient empirical antimicrobial therapy.